2022
DOI: 10.1002/hep4.1943
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of high‐mobility group box‐1 in the liver reduces hepatocellular carcinoma but causes hyperbilirubinemia in Hippo signaling‐deficient mice

Abstract: Silencing the Hippo kinases mammalian sterile 20‐like 1 and 2 (MST1/2) activates the transcriptional coactivator yes‐associated protein (YAP) in human hepatocellular carcinoma (HCC). Hepatocyte‐derived high‐mobility group box‐1 (HMGB1) regulates YAP expression; however, its contribution to HCC in the context of deregulated Hippo signaling is unknown. Here, we hypothesized that HMGB1 is required for hepatocarcinogenesis by activating YAP in Hippo signaling‐deficient (Mst1/2ΔHep) mice. Mst1/2ΔHep mice developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Our study showed that ablation of Hmgb1 reduced the number of F4/80 + cells in Mst1/2 -deficient livers and was associated with reduced HCC proliferation. 26 Here, we observed increased number of F4/80 + cells, at 9 months, and increased F4/80 staining, at 3 months, in Hmgb1 compared to empty AAV8-injected mice. Although not significant, the overall number of F4/80 + cells was increased in Hmgb1 compared to empty AAV8-injected female Pten ∆Hep mice (Figure 6 C, Supplemental Figure S11C–E, http://links.lww.com/HC9/A656 ).…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…Our study showed that ablation of Hmgb1 reduced the number of F4/80 + cells in Mst1/2 -deficient livers and was associated with reduced HCC proliferation. 26 Here, we observed increased number of F4/80 + cells, at 9 months, and increased F4/80 staining, at 3 months, in Hmgb1 compared to empty AAV8-injected mice. Although not significant, the overall number of F4/80 + cells was increased in Hmgb1 compared to empty AAV8-injected female Pten ∆Hep mice (Figure 6 C, Supplemental Figure S11C–E, http://links.lww.com/HC9/A656 ).…”
Section: Resultssupporting
confidence: 50%
“…We reported that HMGB1 expression is higher in primary liver cancer compared to healthy control in the human The Cancer Genome Atlas Liver Hepatocellular Carcinoma cohort. 26 Further analysis of RNA-seq data set GSE107943 from patients with iCCA showed increased expression of HMGB1 in tumor versus nontumor, irrespective of MASH (Figure 1 C). Overall, these observations indicate that HMGB1 transcripts increase in patients with MASH and liver cancer.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…HMGB1 acts as an anti-tumour protein, regulating the immune cell response during the process of carcinogenesis, with the implication that abnormal HMGB1 expression is associated with the oncogenesis, development and metastasis of cancer [88]. According to Athavale et al, ablation of HMGB1 in the liver reduces hepatocellular carcinoma but causes hyperbilirubinaemia in mice deficient in Hippo signalling [89]. Other studies indicate that HMGB1 may be an important marker for assessing tumour staging and predicting prognosis in hepatocellular carcinoma, as HMGB1 levels in hepatocellular carcinoma were significantly higher than in chronic hepatitis, cirrhosis and healthy controls.…”
Section: High-mobility Group Box 1 Protein (Hmgb1; Hmg-1; Amphoterin)mentioning
confidence: 99%